1988
DOI: 10.1039/p19880001263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bibenzyl cannabinoids, hybrids of two biogenetic series found in Cannabis sativa

Abstract: Syntheses of a series of compounds which merge a m-dihydroxybibenzyl with a terpenoid structure, giving a series of hybrid cannabinoids in which products of two major biogenetic routes of Cannabis are united, are described. The compounds made are the bibenzyllo-and p-cannabigerols ( 1 9) and (1 8 ) / 0and p-cannabidiols ( 21) and ( 20),/A'-THC ( 22),/A6-THC ( 23),/0-and p-cannabichromenes (25) and (24),/0and p-cannabicyclols (28) and ( 27) and/cannabicitran (26). Chromatographic and spectral data are listed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Moreover, in liverworts from Radula species the isolation of geranylated bibenzyls analogous to CBG was reported (Asakawa et al 1982), suggesting homology of PKS and prenylase genes from the cannabinoid pathway in other species. Crombie et al (1988) reported the chemical synthesis of bibenzyl cannabinoids.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in liverworts from Radula species the isolation of geranylated bibenzyls analogous to CBG was reported (Asakawa et al 1982), suggesting homology of PKS and prenylase genes from the cannabinoid pathway in other species. Crombie et al (1988) reported the chemical synthesis of bibenzyl cannabinoids.…”
Section: Resultsmentioning
confidence: 99%
“…12 Adduct 11 was confirmed by comparison of its spectral data with those of the known authentic compound. 17 Reactions of 9 with 1-cyclohexene-1-carboxaldehyde and (-)-perillaldehyde in refluxing p-xylene provided adducts 12 and 13 in 60 and 68% yields, respectively, as a single compound, whereas treatment with (-)-myrtenal gave product 14 with 90% diastereoselectivity in 65% yield. The stereochemistry of new compounds 13 and 14 was confirmed by comparison with reported data.…”
Section: Resultsmentioning
confidence: 99%
“…9,10) The structures of the new compounds were determined by careful interpretation of twodimensional NMR spectroscopic data and CD spectral analysis, and those of the known compounds by comparison of their spectral data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The photochemical reaction product, compound 8, displayed stronger activity than its precursor (6). 9,10) The strong inhibition of the prenylated bisbibenzyls and bibenzyl-cannabinoids (3-8, Fig. 4) was suggested to be due to their antioxidant properties.…”
Section: )mentioning
confidence: 99%